2023
DOI: 10.3390/ijerph20053908
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heatwaves on Hospital Admissions for Cardiovascular and Respiratory Diseases, in Southern Vietnam, 2010–2018: Time Series Analysis

Abstract: This study investigated the associations between heatwaves and daily hospital admissions for cardiovascular and respiratory diseases in two provinces in Viet Nam known to be vulnerable to droughts during 2010–2018. This study applied a time series analysis with data extracted from the electronic database of provincial hospitals and meteorological stations from the corresponding province. To eliminate over-dispersion, this time series analysis used Quasi-Poisson regression. The models were controlled for the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Identifying and understanding the health outcomes from climate exposures are important for implementing mitigation strategies for at-risk populations in order to reduce future extreme weather-related risks. Numerous studies and assessments have tried to assess the health effects of climate-related exposures, including heat, extreme precipitation, and air quality [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. We refer here to two recent review articles that have assessed the risk to human health posed by extreme weather and climate exposures with regard to their public health implications [ 5 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying and understanding the health outcomes from climate exposures are important for implementing mitigation strategies for at-risk populations in order to reduce future extreme weather-related risks. Numerous studies and assessments have tried to assess the health effects of climate-related exposures, including heat, extreme precipitation, and air quality [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. We refer here to two recent review articles that have assessed the risk to human health posed by extreme weather and climate exposures with regard to their public health implications [ 5 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heatwaves are defined as extended periods lasting three or more consecutive days, during which average temperatures exceed the 95th percentile value of local temperatures [2]. The anticipated effects of climate change on heat stress conditions are expected to result in increased mortality rates and diminished labor productivity, particularly among vulnerable populations [3][4][5]. These impacts often remain unnoticed initially, because of their delayed and inconspicuous nature.…”
Section: Introductionmentioning
confidence: 99%
“…Vietnam has incurred substantial economic costs due to mortality resulting from heatwaves, reaching USD 11.72 billion (i.e., 34,271 deaths at the value of statistical life of USD 0.342 million) from 2003 to 2017 [7]. Over the past four decades, Vietnam has witnessed a notable climate shift characterized by a significant temperature increase [4,8]. Among the regions within Vietnam, the southeast, central highlands, and south-central coast areas are particularly susceptible to the impact of heatwaves [2,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a systematic review and meta-analysis by Faurie and colleagues, a 1 • C increase in temperature raised heat-related illness hospitalisation rates by 18% [51]. Some recent studies also have found positive relationships between heatwaves and hospital admissions [33,[52][53][54][55][56]. However, little research has been conducted on the association between heatwaves and hospitalisations in one-season regions.…”
Section: Introductionmentioning
confidence: 99%